Characteristics of gastric fluid microbiota in patients with refractory Helicobacter pylori infection - Zhu, Huiting; Sun, Shijie; Wang, Yujing; Zhang, Wensi; Du, Shiyu; Zhang, Yanli (Frontiers in Microbiology, 2025)
IntroductionRefractory Helicobacter pylori infection (RHPI) poses a clinical challenge due to its treatment resistance. The gastric microbiota characteristics in patients with RHPI remain unclear. This study analyzed gastric fluid samples to explore the structural and functional differences in the gastric microbiota of patients with RHPI and their association with clinicopathological features, providing a theoretical basis for precision treatment of RHPI.MethodsEighty-four patients who underwent gastroscopy were prospectively and consecutively divided into the Nhp (H. pylori-negative, n = 32), Php (H. pylori-positive at first diagnosis without treatment, n = 32), and Rhp (RHPI, n = 20) groups. Gastric fluid and mucosal biopsy samples were collected for 16S rRNA gene sequencing, pathological evaluation, and bioinformatic analysis. Differences in gastric microbiota and clinical data were compared among the three groups.ResultsThe Rhp group exhibited more gastric mucosal atrophy, inflammation, and inflammatory activity than Nhp and Php groups. Rhp also showed lower microbial richness and diversity. β-diversity analysis revealed distinct microbial communities between the Nhp and Php/Rhp groups. Rhp was enriched with H. pylori PZ5004 and Pseudoalteromonas sp. C_8, among others, while Php was enriched with Lactobacillus sp. CY1 and other species and Nhp with Prevotella melaninogenica and other species. The Rhp group also had higher H. pylori PZ5004/P79 abundance, more complex microbial interactions, and enriched sulfur relay pathways than the other groups.ConclusionH. pylori infection disrupts the diversity, structure, and function of gastric microbiota. The close interaction between characteristic microbiota and H. pylori subspecies may be a key factor contributing to the difficulty in treating RHPI.